PENGARUH MOTIVASI TERHADAP SEMANGAT KERJA KERYAWAN PT.ADHYASHTA PALEMBANG - Azizah; Indriani (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2023)
Motivation is one of several factors that can affect employee morale. Motivation itself is divided into two types, namely, intrinsic motivation and extrinsic motivation. Intrinsic motivation is a driving force for work that comes from within the worker as an individual, while extrinsic motivation is someone who has passion at work means also has the motivation and drive to work. This research was conducted using the Simple Linear Regression analysis tool, t test to analyze the closeness of the relationship between different variables. The purpose of this study was to determine the effect of work motivation on morale at PT Adhyashta Palembang. From the results of the t test, the regression equation is obtained: Y = 3.496 + 0.854. Then, from the calculation of the correlation coefficient, a value of 0.807 is obtained which indicates that there is a close relationship between the variables of motivation (X) and morale (Y). To find out that there is a significant effect of the independent variables on the dependent variables, the t test is used where it is known that 0.00 <0.005 so that the meaning of the motivational spirit variable is significantly related to the morale variable.